2000
DOI: 10.1053/he.2000.5746
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cisapride on intestinal bacterial overgrowth and bacterial translocation in cirrhosis

Abstract: Deranged intestinal motility, which occurs in cirrhosis, may facilitate the development of intestinal bacterial overgrowth (IBO), which can lead to bacterial translocation (BT). To assess the effect of cisapride on IBO and BT in cirrhosis, cirrhotic rats received cisapride or a placebo for 7 days, and measurements of jejunal bacterial content and BT studies were performed. In addition, jejunal fluid from 46 cirrhotic patients was obtained for quantitative bacterial culture. Those patients in whom gram-negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
106
0
6

Year Published

2001
2001
2007
2007

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(117 citation statements)
references
References 37 publications
5
106
0
6
Order By: Relevance
“…We found evidence that factors other than endotoxin influence circulating levels of TNF-␣ and sTNFRs in patients with cirrhosis. Evidence that Gram-positive microbial stimuli may be implicated is consistent with recent reports of a high prevalence of intestinal bacterial overgrowth with Gram-positive bacteria in cirrhotic patients [24][25][26] and findings implying increased translocation of lipoteichoic acid from the intestine in this group. 27 Consequently, we investigated the possible importance of Gram-positive gut flora by studying systemic TLR expression and TNF-␣ levels along with in vitro production of TNF-␣ in cirrhotic patients before, during, and after oral supplementation with a synbiotic (probiotic and prebiotic) regimen that included bacterial species known to enhance intestinal levels of Gram-positive bacteria.…”
supporting
confidence: 91%
“…We found evidence that factors other than endotoxin influence circulating levels of TNF-␣ and sTNFRs in patients with cirrhosis. Evidence that Gram-positive microbial stimuli may be implicated is consistent with recent reports of a high prevalence of intestinal bacterial overgrowth with Gram-positive bacteria in cirrhotic patients [24][25][26] and findings implying increased translocation of lipoteichoic acid from the intestine in this group. 27 Consequently, we investigated the possible importance of Gram-positive gut flora by studying systemic TLR expression and TNF-␣ levels along with in vitro production of TNF-␣ in cirrhotic patients before, during, and after oral supplementation with a synbiotic (probiotic and prebiotic) regimen that included bacterial species known to enhance intestinal levels of Gram-positive bacteria.…”
supporting
confidence: 91%
“…Nonantibiotic procedures could also be effective in the prevention of infections in cirrhotic patients. 55 We conclude that prophylaxis with norfloxacin favors the development of infections caused by norfloxacin-resistant E. coli, mainly in patients on continuous long-term prophylaxis. This finding speaks against the widespread use of prophylaxis, that should be restricted to highly selected groups at high risk of infection closely monitored for the development of bacterial resistance.…”
Section: Discussionmentioning
confidence: 76%
“…41 The major concern with the use of prolonged antibiotic prophylaxis is that it will lead to selection of antibioticresistant bacteria. 42,43 Recent studies have shown that bacterial overgrowth and bacterial translocation can also be decreased in experimental cirrhosis by accelerating intestinal transit with cisapride 14 or with propranolol. 44 However, cisapride can produce QT interval prolongation and ventricular arrhythmias.…”
Section: Discussionmentioning
confidence: 99%